2001
DOI: 10.1016/s0370-1573(00)00131-9
|View full text |Cite
|
Sign up to set email alerts
|

Neutrino emission from neutron stars

Abstract: We review the main neutrino emission mechanisms in neutron star crusts and cores. Among them are the well-known reactions such as the electron-positron annihilation, plasmon decay, neutrino bremsstrahlung of electrons colliding with atomic nuclei in the crust, as well as the Urca processes and neutrino bremsstrahlung in nucleon-nucleon collisions in the core. We emphasize recent theoretical achievements, for instance, band structure effects in neutrino emission due to scattering of electrons in Coulomb crystal… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
349
1
3

Year Published

2006
2006
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 549 publications
(363 citation statements)
references
References 187 publications
5
349
1
3
Order By: Relevance
“…For the hadronic phase, the neutrino emission processes considered in this work are the direct Urca, modified Urca and bremsstrahlung processes. A detailed review of the emissivities of such processes can be found in reference [40]. We note that the neutrino emission involving neutrons, and the neutron specific heat are exponentially suppressed as the temperature drops below the neutron superfluidity critical temperature.…”
Section: Resultsmentioning
confidence: 96%
“…For the hadronic phase, the neutrino emission processes considered in this work are the direct Urca, modified Urca and bremsstrahlung processes. A detailed review of the emissivities of such processes can be found in reference [40]. We note that the neutrino emission involving neutrons, and the neutron specific heat are exponentially suppressed as the temperature drops below the neutron superfluidity critical temperature.…”
Section: Resultsmentioning
confidence: 96%
“…II A and (26)). This assumption makes sense because of the slowness of the electroweak reactions responsible for the chemical equilibrium [53], added to the fact that the two fluids are likely to be always very close to corotation 2 Assuming the total angular momentum to be constant during a…”
Section: B Two-fluid Hydrodynamicsmentioning
confidence: 99%
“…(13) Hence, if M 2 is known, the total neutrino emissivity from e + e − plasma can be calculated by performing appropriate integrations [13]:…”
Section: Pair Annihilation In the Standard Modelmentioning
confidence: 99%